Peningkatan Motivasi Belajar Siswa melalui Penerapan Metode Demonstrasi dalam Pembelajaran Fikih Thaharah di MTs Hidayatud Diniyah - Ismail, Moh.; Yunus, Moh.; Soleh, Soleh; Yuni Lestari, Niken (CV. Satria Jaya, 2024)
This study aims to investigate application of the demonstration method can enhance student learning motivation in Fiqh Thaharah lessons at MTs Hidayatud Diniyah. This research employs a qualitative approach with a case study method. Data were collected through observation, interviews, and questionnaires, then analyzed descriptively. The results showed that the demonstration method created an active and communicative learning environment. Students became more enthusiastic in participating in question-and-answer sessions, showing increased active participation and understanding of the material. Before the demonstration method was applied, the written test evaluation showed that only 40% of students achieved the ideal score, while 60% did not meet the minimum completion standard. However, after the demonstration method was implemented, 92.5% of students were able to perform the wudhu practice correctly, showing a significant improvement of 65.2%.